Through-thickness electric conductivity of toughened carbon-fibre-reinforced polymer laminates with resin-rich layers. (18th January 2016) - Hirano, Yoshiyasu; Yamane, Takuya; Todoroki, Akira
Abstract: Self-sensing carbon-fibre-reinforced polymer (CFRP) that use changes in electrical resistance has been applied to monitor delamination cracks in CFRP composite structures. CFRP laminated composites have orthotropic electric conductivity. Despite the existence of insulator resin-rich layers between each ply, the toughened CFRP laminates have electric conductivity in the thickness direction, which plays important role in delamination monitoring with changes in electrical resistance. Further more, it is also quite important to understand the lightning damage behaviour of CFRP laminate and to perform numerical simulations estimating the current flow in CFRP laminate when lightning event. However, the measured electric conductance has not been confirmed to be a material property for toughened CFRP. The objective of the present study is thus to clarify the mechanism of realizing electric conductivity in the through-thickness direction. During the curing process, alternating current is applied, and impedance is measured for toughened CFRP. It is found that conductivity in the through-thickness direction of toughened CFRP laminates is due to chance carbon fibre contact between plies during the curing process, and is not a material property.